2017
DOI: 10.15406/acp.2017.02.00010
|View full text |Cite
|
Sign up to set email alerts
|

Prospects of Essential Oils in Drug Discovery

Abstract: Essential oils (EO), according to the International Standard Organization (ISO) defines essential oil as the product obtained from parts of plants by distillation with water steam and the product obtained by expression from pericarp of medicinal plant. The rapid growth and increase of the knowledge of identification, extraction, purification and characterization of essential oils in most local plant species is fast becoming an important aspect of the drug production process. Despite the complex nature of the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…In the kidney of two rats were observed cortical haemorrhage and protein casts in the tubular lumen of one rat. In the liver of four rats were observed portal cellular infiltration (penetration of cells in an area) [3]. In the control animals (group D), it was observed that there was no harmful damage seen in the brains, kidneys, hearts and testis of all rats as was the case in group A.…”
Section: Severe Interstitial Oedemamentioning
confidence: 65%
See 2 more Smart Citations
“…In the kidney of two rats were observed cortical haemorrhage and protein casts in the tubular lumen of one rat. In the liver of four rats were observed portal cellular infiltration (penetration of cells in an area) [3]. In the control animals (group D), it was observed that there was no harmful damage seen in the brains, kidneys, hearts and testis of all rats as was the case in group A.…”
Section: Severe Interstitial Oedemamentioning
confidence: 65%
“…sesame oil), other have medicinal action e.g. castor oil (as a cathartic) and liver oil (as an emollient), [2,3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…29 Antimicrobial compounds that act on the membrane can cause depolarization or increased permeability through various mechanisms. For example, the extracted essential oil from S. mombin, some antimicrobial peptides form pores 30,31 while other compounds, such as certain essential oil constituents, have a fluidifying effect on the membrane. From the results of the assessment of antimicrobial activities of the pure isolated compounds on selected test organisms (Table 6).…”
Section: Resultsmentioning
confidence: 99%
“…Natural products have no or fewer side effects [12,13] compared to synthetic chemicals that are blended with food products [13]. In recent years, scientific research has focused more in discovering and identifying local plant species with bioactive compounds as an essential oil, their characterization, extraction and purification processes and application in drug industries [14]. Presently 25 to 50% of drugs are available from plants [15] and numerous other aromatic plants are under evaluation for their valuable essential oil [13].…”
Section: Plant Essential Oil-an Alternative To Mdr Microbesmentioning
confidence: 99%